A proposal of excercises to improve students´ pronunciation in 9th graders from José Martí secondary school in Sagua la Grande - Águila Ruiz, Dayana (Universidad Central "Marta Abreu" de Las Villas, 2016)
After a long process of research, it was confirmed that students face some pronunciation problems which affect their accuracy when communicating. Thus, the main goal of this paper is to build up a system of exercises to work with students´ pronunciation from group 9.2 at “José Martí” Secondary School.To achieve the objective of this study, it was necessary to use several methods of research.Some empirical methods such as participant observation, pedagogical test, interview to students, teacher`s diary, discussion group and triangulation were used to gather the necessary data about the current situation of the subjects of research, as well as for the constructing process of the proposal.The proposal is the result of a building up process in which the suggestions given by the discussion group and the experiences recorded in the teacher´s diary were taken into account to obtain the final scientific result. It is a system of exercises aimed at enhancing students´ pronunciation.
Keywords: Communicative; Secondary School; Proposal of Excercises; Pronunciation